Some short-run macroeconomic considerations as society deals with a once-in-generations pandemic - Arslan Razmi (University of Massachusetts, Department of Economics, 2020)
COVID-19 constitutes a health crisis which has rapidly turned into a social and economic crisis. This paper briefly explores some of the issues raised by the combination of a massive supply-side shock with a massive demand-side shock, and the interaction of these with the exponential dynamics of a viral infection. The analysis suggests that, during the recovery, the state of infection among the existing workforce relative to that of the incoming one will play an important role in determining the dynamic interactions between economics and epidemiology. Perhaps counterintuitively, the logic of the basic epidemiological SI model suggests that, under plausible assumptions about consumer behavior, steady recovery is helped if the re-hired workers are more heavily infected than the existing workforce. This has implications for the fiscal strategies that are likely to be pursued in the coming months. In particular, fiscal instruments should simultaneously target aggregate demand and disease transmissibility in relatively small steps. There is no restoring economic health without stabilizing economic sentiments, the path to which goes through communicating a reasonable degree of control over pathogen spread.
Keywords: E62; H51; E60; 330; Epidemiological models; COVID-19; aggregate demand; aggregate supply; fiscal policy